Growth Factors in Fibrotic Diseases - Deuel, Thomas F; Senior, Robert M (The New England journal of medicine, 1987)
IN this issue Martinet et al. 1 report that alveolar macrophages from patients with idiopathic pulmonary fibrosis release a growth-promoting activity similar to platelet-derived growth factor (PDGF), and show that the amount of this activity is four times greater than that of the PDGF-like activity released from alveolar macrophages from normal subjects. Assays of chemotaxis and growth-promoting activity established that the mitogen secreted from macrophages was active, and the identity of the secreted activity was suggested by receptor-competition assays and by blockade of its biologic activity with anti-PDGF serum. The results are important, correlating an increased level of a secreted growth . . .